Health needs and perception of health care quality among Asylum Seekers and Refugees in an Italian local health authority: A qualitative study - Marchetti, Francesca; Preziosi, Jessica; Zambri, Francesca; Tambascia, Gabriella; Di Nolfi, Annachiara; Scardetta, Paola; Splendore, Flavia; Colaceci, Sofia; Coia, Maura; Caredda, Emanuele; Masi, Loredana; De Luca, Vittorio; et al. (Frontiers in Public Health, 2023)
Background Migrants, Asylum Seekers and Refugees (ASRs) represent a vulnerable diversified population with increased risks of developing health problems, and in the hosting countries several barriers often hamper their access to the health services. Gathering information about ASRs’ experiences and perceptions of host country health care systems may contribute to improve the quality of health care provided. The aim of this study was to explore the health needs in their bio-psycho-social meaning, and the quality of health care as perceived from the ASRs’ perspective. Methods The qualitative descriptive study was conducted as part of the Project “G-START – testing a governance model of receiving and taking care of the Asylum Seekers and Refugees.” Through purposeful and snowball sampling, four Focus Groups conducted in English, Italian and French were carried out between July and August 2019, involving 50 ASRs hosted by four reception centers located on the territory pertaining to an Italian Local Health Authority covering a general population of 500.000 people. The analysis of data was categorical, and was performed using N-Vivo software. Results The macro-categories emerged were the ASRs’ bio-psycho-social health needs, including mental health, sexual and reproductive health, food and nutrition, knowledge of the health care system, need for inclusion; healthcare services access, including barriers before and after the access and the ability of the local health system to respond to existing and evolving demands; strengths of the healthcare and reception systems, and suggestions for improving them in the future. Discussion and conclusions ASRs present vulnerabilities and specific health needs, and the health care system is not always able to guarantee access or to respond to these needs. Several obstacles have been highlighted, such as linguistic barriers and lack of cultural mediation, bureaucratic and administrative barriers, lack of knowledge of the Italian health care system. An effective reorganization of services driven by a more detailed output analysis of the target population needs, together with the use of cultural mediation, peer to peer education and support, and the training of health professionals are recommended to ensure a more accessible, equitable and effective health care system at local level.